hmwk10sol2027 - Solutions to Homework 10, ISyE 2027 Fall...

Info iconThis preview shows pages 1–3. Sign up to view the full content.

View Full Document Right Arrow Icon
Solutions to Homework 10, ISyE 2027 Fall 2006 Problem 1 (a) geometric (b) Poisson (c) binomial (d) normal (e) exponential Problem 2 (a) P ( Z 1 . 44) = 0 . 9251. (b) We see that P ( | Z | ≤ 1 . 44) = P ( - 1 . 44 Z 1 . 44) = P ( Z 1 . 44) - P ( Z ≤ - 1 . 44) = 2 P ( Z 1 . 44) - 1 = 0 . 8502 . (c) P ( Z > 1 . 44) = 1 - P ( Z 1 . 44) = 0 . 0749. (d) P ( Z = 1 . 44) = 0 ( Z is continuous). (e) We see that 0 . 05 = P ( | Z | > x ) = P ( Z x ) + P ( Z ≤ - x ) = 2 P ( Z x ) = 2(1 - P ( Z x )) . This implies that P ( Z x ) = 0 . 975. After using a normal table, we see that x = 1 . 96. Problem 3 Now suppose X N (2 , 100). Then (a) P ( X 9) = P (10 Z + 2 9) = P ( Z . 7) = 0 . 7580. (b) P ( | X | > 9) = 1 - P ( | X | ≤ 9) = 1 - P ( - 9 X 9) = 1 - P ( - 9 10 Z + 2 9) = 1 - P ( - 1 . 1 Z 0 . 7) = 2 - P ( Z 0 . 7) - P ( Z 1 . 1) = 0 . 3777 . (c) Now, 0 . 05 = P ( | X - 2 | ≥ 3 x ) = P ( X - 2 3 x ) + P ( X - 2 ≤ - 3 x ) = P (10 Z 3 x ) + P (10 Z 3 x ) = 2 P ( Z 0 . 3 x ) so now we find that P ( Z 0 . 3 x ) = 0 . 975 1
Background image of page 1

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
which implies that 0 . 3 x = 1 . 96, or x = 6 . 533. Problem 4 Here P ( μ - kσ < Y < μ + ) = P ( μ - kσ < μ + σZ < μ + ) = P ( - k < Z < k ) = 2 P ( Z k ) - 1 . If k = 0, the probability is 0. If k = 1, the probability is 0.6826. If k = 2, the probability is 0 . 9544. Finally, if k = 3, the probability is 0 . 9974. Problem 5 Using the formula given for the even moments of a standard normal r.v., we see that E [ Z 2 ] = 1 and E [ Z 4 ] = 3 (we’ll use these later). (a) The mean of X n is just E [ X n ] = E [ n X k =1 Z 2 k ] = n X k =1 E [ Z 2 k ] = nE [ Z 2 1 ] = n. The variance of X n is V ar ( X n ) = V ar ( n X k =1 Z 2 k ) = n X k =1 V ar ( Z 2 k ) = nV ar ( Z 2 1 ) . But V ar ( Z 2 1 ) = E [ Z 4 1 ] - E [ Z 2 1 ] 2 = 3 - 1 = 2, so V ar ( X n ) = 2 n . (b) Now
Background image of page 2
Image of page 3
This is the end of the preview. Sign up to access the rest of the document.

This note was uploaded on 02/01/2010 for the course ISYE 2027 taught by Professor Zahrn during the Spring '08 term at Georgia Institute of Technology.

Page1 / 8

hmwk10sol2027 - Solutions to Homework 10, ISyE 2027 Fall...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online